2002
DOI: 10.1016/s0014-5793(02)02889-2
|View full text |Cite
|
Sign up to set email alerts
|

Leptin receptor isoform expression in rat osteoblasts and their functional analysis

Abstract: The genetic defect in producing the adipose hormone leptin results among others in a drastic increase of bone mass. The current understanding is that under normal circumstances, osteoblast activity is indirectly suppressed by a hypothalamic relay induced by leptin-signalling in the brain. To investigate whether leptin might also regulate osteoblast activity in a direct manner, expression of leptin receptors in rat osteoblasts was determined and their functionality was analyzed upon recombinant leptin treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 20 publications
2
37
0
1
Order By: Relevance
“…Therefore, although evidence for a role of the central and sympathetic nervous systems in mediating the suppressive actions of leptin on bone is compelling (Ducy et al 2000, Hamrick & Ferrari 2007, our data combined with that demonstrating that leptin enhances osteoblast number and activity in vitro (Thomas et al 1999, Lee et al 2002 indicate that a positive direct action of leptin in bone cannot be excluded.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, although evidence for a role of the central and sympathetic nervous systems in mediating the suppressive actions of leptin on bone is compelling (Ducy et al 2000, Hamrick & Ferrari 2007, our data combined with that demonstrating that leptin enhances osteoblast number and activity in vitro (Thomas et al 1999, Lee et al 2002 indicate that a positive direct action of leptin in bone cannot be excluded.…”
Section: Discussionmentioning
confidence: 81%
“…Supra-physiological levels of leptin are thought to suppress bone formation by a centrally mediated pathway involving the hypothalamus and the sympathetic nervous system (Ducy et al 2000, Hamrick & Ferrari 2007, while leptin within the normal range increases osteoblast number and enhances osteoblast activity via a direct mechanism (Thomas et al 1999, Lee et al 2002. Indeed, it has been reported that the leptin receptor (Hamrick et al 2005) and even leptin itself (Laharrague et al 1998) are both expressed in bone.…”
Section: Discussionmentioning
confidence: 99%
“…vator SRC-1 and osteogenic transcription factor Runx2, transactivates osteocalcin, one of the Runx2 downstream target genes that may in turn mediate the osteogenic activity of leptin. STAT3 plays an essential role during embryonic development, cell survival, and differentiation (39). At the molecular level, STAT3 acts as a transcription activator and interacts with other nuclear factors to regulate a number of genes that are critically involved in cell proliferation and differentiation (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Such peptides include substance-P, VIP, CGRP and neuropeptide-Y (25,26), as well as leptin and the endogenous ligand of growth hormone secretagogue (GHS) receptor ghrelin, which, like orexins, play a major role in the central control of energy homeostasis. Evidence has been provided that leptin is expressed in and secreted from human osteoblasts in primary culture (27)(28)(29), and that functionally active leptin-receptor isoforms are present in human osteoblast-derived cell lines and rat osteoblasts (30,31). Leptin was found to enhance human marrow stromal cell differentiation into osteoblasts (32), to stimulate proliferation of cultured osteoblasts, and to promote matrix production and mineralization (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%